Comparison of Staphylococcus aureus tolerance between antimicrobial blue light, levofloxacin, and rifampin - Ong, Jemi; Godfrey, Rose; Nazarian, Alexa; Tam, Joshua; Isaacson, Brad M.; Pasquina, Paul F.; Williams, Dustin L. (Frontiers in Microbiology, 2023)
Background Bacterial biofilms readily develop on all medical implants, including percutaneous osseointegrated (OI) implants. With the growing rate of antibiotic resistance, exploring alternative options for managing biofilm-related infections is necessary. Antimicrobial blue light (aBL) is a unique therapy that can potentially manage biofilm-related infections at the skin-implant interface of OI implants. Antibiotics are known to have antimicrobial efficacy disparities between the planktonic and biofilm bacterial phenotypes, but it is unknown if this characteristic also pertains to aBL. In response, we developed experiments to explore this aspect of aBL therapy. Methods We determined minimum bactericidal concentrations (MBCs) and antibiofilm efficacies for aBL, levofloxacin, and rifampin against Staphylococcus aureus ATCC 6538 planktonic and biofilm bacteria. Using student t-tests (p < 0.05), we compared the efficacy profiles between the planktonic and biofilm states for the three independent treatments and a levofloxacin + rifampin combination. Additionally, we compared antimicrobial efficacy patterns for levofloxacin and aBL against biofilms as dosages increased. Results aBL had the most significant efficacy disparity between the planktonic and biofilm phenotypes (a 2.5 log10 unit difference). However, further testing against biofilms revealed that aBL had a positive correlation between increasing efficacy and exposure time, while levofloxacin encountered a plateau. While aBL efficacy was affected the most by the biofilm phenotype, its antimicrobial efficacy did not reach a maximum. Discussion/conclusion We determined that phenotype is an important characteristic to consider when determining aBL parameters for treating OI implant infections. Future research would benefit from expanding these findings against clinical S. aureus isolates and other bacterial strains, as well as the safety of long aBL exposures on human cells.